2022
DOI: 10.54548/njps.v37i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin normalizes blood pressure via its antioxidant activity and down-regulation of renal Angiotensin II receptor and Mineralocorticoid receptor expressions in rats co-exposed to Diclofenac and sodium fluoride

Abstract: This study was designed to investigate the modulatory role of Luteolin (Lut), a flavonoid phytochemical, on haemodynamic parameters and the potential mechanisms involving renal Angiotensin II (AT2R) and Mineralocorticoid (MCR) receptors in renal toxicity induced by co-exposure to Diclofenac (Dcf) and sodium fluoride (NaF) in rats.Male Wistar rats were administered with either vehicle (control), Dcf only (9 mg/kg orally) or concurrently with NaF (300 ppm in drinking water). Other groups were treated with LutA (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Its biological activities include anti-inflammatory, antioxidant, and cytotoxic effects, which are mediated through in vivo anti-inflammatory and antioxidant mechanisms. These mechanisms have been shown to effectively mitigate cellular damage ( Ajibade et al, 2022 ; Caporali et al, 2022 ). Previous research has demonstrated that Lut exhibits the potential to mitigate the presence of inflammatory mediators through the elimination of free radicals, thereby offering therapeutic benefits in the treatment of carbon tetrachloride ( Habibi et al, 2021 ), mercury ( Tan et al, 2018 ), arsenic ( Quiller et al, 2018 ), and lead ( Baty et al, 2020 ) poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…Its biological activities include anti-inflammatory, antioxidant, and cytotoxic effects, which are mediated through in vivo anti-inflammatory and antioxidant mechanisms. These mechanisms have been shown to effectively mitigate cellular damage ( Ajibade et al, 2022 ; Caporali et al, 2022 ). Previous research has demonstrated that Lut exhibits the potential to mitigate the presence of inflammatory mediators through the elimination of free radicals, thereby offering therapeutic benefits in the treatment of carbon tetrachloride ( Habibi et al, 2021 ), mercury ( Tan et al, 2018 ), arsenic ( Quiller et al, 2018 ), and lead ( Baty et al, 2020 ) poisoning.…”
Section: Introductionmentioning
confidence: 99%